2020
DOI: 10.17509/ijost.v5i3.26139
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Forecasting of the COVID-19 Epidemic using the Richards Model in South Sulawesi, Indonesia

Abstract: This paper discussed Real-time Forecasting of the COVID-19 Epidemic using daily cumulative cases of COVID-19 in South Sulawesi. Our aim is to make model for the growth of COVID-19 cases in South Sulawesi in the top 5 provinces with the largest COVID-19 cases in Indonesia and predict when this pandemic reaches the peak of spread and when it ends. This paper used the Richards model, which is an extension of a simple logistic growth model with additional scaling parameters. Data used in the paper as of June 24, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…Most countries around the world went into lockdown to reduce the spread of COVID-19. Several studies showed that the coronavirus pandemic is expected to end in December 2020 (Zuhairoh and Rosadi, 2020). However, until July 2021, we are still facing this issue with a new more contagious variant.…”
Section: Introductionmentioning
confidence: 99%
“…Most countries around the world went into lockdown to reduce the spread of COVID-19. Several studies showed that the coronavirus pandemic is expected to end in December 2020 (Zuhairoh and Rosadi, 2020). However, until July 2021, we are still facing this issue with a new more contagious variant.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the Richards model has been previously studied by Hsieh (2009Hsieh ( , 2010 in SARS and H1N1 disease outbreaks. We have also used the Richards model for the COVID-19 outbreak in South Sulawesi, Indonesia (Zuhairoh and Rosadi, 2020), where the results accurately predict the pattern of the spread of COVID-19 cases. Furthermore, Wang et al (2016) developed the gray Richards model to get the predicted results of Growth of Rice Leaves and Amoeba Cell Growth.…”
Section: Introductionmentioning
confidence: 99%
“…These include poverty, that further disrupted sustainable livelihoods, hunger and disease, increasing socio-economic disparities attributable to educational disparities, alienation and foreign policy [1][2][3] and they affect the responses in critical policy areas, including public health directives and financial responses. In the presence of such obstacles, each nation uses its own strategies [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%